Odpowiedzi

2010-01-24T11:45:54+01:00
2x-3y=5
2x+3y=3

-3y=5-2x
3y=3-2x
o=8-4x
4x=8/:4
x=2

-3y=5-2*2
-3y=1
y=-1/3

czyli (2; -1/3) odp. d
4 2 4
Najlepsza Odpowiedź!
2010-01-24T11:49:16+01:00
A) x = 1 , y = -1

2x - 3y = 5
2 * 1 - 3 * (-1) = 5
2 + 3 = 5

ale

2x + 3y = 3
2 * 1 + 3 * (-1) = 3
2 + 3 = 3
5 = 3
czyli A odpada.

b) odpada, bo np. para liczb ( 1, -1 ) nie spełnia równania.

c) x = -3 , y = 1

2x - 3y = 3
2 * (-3) - 3 * 1 = 3
- 6 - 3 = 3
- 6 = 3
C też odpada .

ODPOWIEDZ D jest prawidłowa ;)

5 4 5